The Expediency of Culture Uses of Culture in the Global Era - Yúdice, George (Post-Contemporary Interventions, 2004)
The Expediency of Culture is a pioneering theorization of the changing role of culture in an increasingly globalized world. George Yúdice explores critically how groups ranging from indigenous activists to nation-states to nongovernmental organizations have all come to see culture as a valuable resource to be invested in, contested, and used for varied sociopolitical and economic ends. Through a dazzling series of illustrative studies, Yúdice challenges the Gramscian notion of cultural struggle for hegemony and instead develops an understanding of culture where cultural agency at every level is negotiated within globalized contexts dominated by the active management and administration of culture.